The Biogenic Synthesis of Bimetallic Ag/ZnO Nanoparticles - Afzal, Muhammad Asjad (2023)
Funding Information: M.B.T acknowledges support from HEC (Higher Education Commission) of Pakistan. S.A.C.C. acknowledges support for the Scientific Employment Stimulus—Institutional Call (CEECINST/00102/2018). Publisher Copyright: © 2023 by the authors.